Pediatric Medication Errors. Issue 2 (March 2017) - Beal, Judy A.
Abstract : Pediatric mediation errors continue to be a risk of harm. The American Academy of Pediatrics has recommendations for giving liquid medications orally. Kitchen spoons are not appropriate to measure doses. Liquid medication should only be administered by an oral syringe that is metric based. Our pediatric nursing expert, Dr. Beal, explains how nurses can play an important role in teaching parents how to safely give medications to their children.